2024
DOI: 10.3390/polym16030320
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Polylactic Acid with Organic Nucleating Agents under Quiescent Conditions

Peng Gao,
Saeed Alanazi,
Davide Masato

Abstract: Polylactic acid (PLA) is a versatile and sustainable polymer used in various applications. This research explores the use of orotic acid (OA) and ethylene bis-stearamide (EBS) as nucleating agents to enhance the quiescent crystallization of PLA within the temperature range of 80 °C to 140 °C. Different blends were produced via melt processing before analyzing via DSC, XRD, and SEM. Our results show that both nucleating agents significantly accelerated the crystallization process and reduced the incubation time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The n values of the composites steadily decreased and the k values significantly increased as the PPZn content increased, supporting a conclusion that the addition of PPZn improved the crystallization properties of PLLA-PEG-PLLA matrices [48,49]. All of the n values were higher than 2.0, suggesting a heterogeneous nucleation effect [50]. The DSC results from both non-isothermal and isothermal scans justified a conclusion that the PPZn acted as a good nucleating agent to increase the crystallinity of PLLA-PEG-PLLA.…”
Section: Thermal Transition Propertiessupporting
confidence: 61%
See 1 more Smart Citation
“…The n values of the composites steadily decreased and the k values significantly increased as the PPZn content increased, supporting a conclusion that the addition of PPZn improved the crystallization properties of PLLA-PEG-PLLA matrices [48,49]. All of the n values were higher than 2.0, suggesting a heterogeneous nucleation effect [50]. The DSC results from both non-isothermal and isothermal scans justified a conclusion that the PPZn acted as a good nucleating agent to increase the crystallinity of PLLA-PEG-PLLA.…”
Section: Thermal Transition Propertiessupporting
confidence: 61%
“…The crystalline structures of film samples were investigated from XRD patterns, as shown in Figure 5. The pure PLLA-PEG-PLLA in Figure 5a had a broad XRD peak at 16.9 • due to PLLA end-block crystallites [47,50]. For the composite films in Figure 5b-e, the XRD peaks of added PPZn were detected at 6.5 • , 12.6 • , and 18.5 • .…”
Section: Crystalline Structuresmentioning
confidence: 98%
“…However, compared to PBS, the enhancement was limited for PCL and PBAT on quiescent conditions. Previous research from the authors showed that under quiescent conditions, the use of orotic acid (OA) and EBS could lead to a higher degree of crystallinity at lower temperatures, smaller and more evenly distributed crystalline structures, a faster crystallization rate, lower crystallization temperature, and lower crystallization half-time when compared to neat PLA [ 132 ].…”
Section: Materials Innovations In Plamentioning
confidence: 99%
“…The parameter represents the time needed to attain 50% of the final crystallinity. Many research articles have reported long crystallization half-times for neat PLA materials [ 32 , 39 , 45 , 74 , 132 , 140 ]. However, annealing at the ideal temperature significantly reduced the crystallization half-time.…”
Section: Processing Optimization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation